The East Pacific/South Pacific Boundary: New taxa and occurrences from Rapa Nui (Easter Island), New Caledonia and adjacent regions - Mah, Christopher L. (Zootaxa, 2021)
Recent expeditions to Rapa Nui (also known as Easter Island) and New Caledonia have revealed undescribed species from mesophotic and deeper depths. This includes three new species from Rapa Nui, Hacelia raaraa, Linckia profunda (Ophidiasteridae), Uokeaster ahi (Asterodiscididae) and two new species from New Caledonia, Astroglypha pyramidata n. gen. and Ophidiaster colossus (Ophidiasteridae). The new genus Astroglypha is described for A. pyramidata but the genus also includes the Atlantic Tamaria passiflora, which is reassigned herein. Pauliastra n. gen. is designated as a replacement for the homonym issue with Pauliella. New occurrences and synonymies are addressed for taxa related to New Caledonia, Rapa Nui and adjacent regions. A morphology based phylogenetic analysis agrees with prior work which placed Goniaster among the Asterodiscididae and posits biogeographic relationships among asterodiscidid genera. Implications for the Goniasteridae and placement of Goniaster among asterodiscidid genera are discussed. Biogeography and relationships among taxa from Rapa Nui and New Caledonia are reviewed. In situ observations from species observed from Rapa Nui are included.